Dominant portion of thyrotropin-releasing hormone receptor is excluded from lipid domains. Detergent-resistant and detergent-sensitive pools of TRH receptor and Gqalpha/G11alpha protein - Rudajev, Vladimir; Novotny, Jiri; Hejnova, Lucie; Milligan, Graeme; Svoboda, Petr (Journal of biochemistry, 2005)
Some G protein-coupled receptors might be spacially targetted to discrete domains within the plasma membrane. Here we assessed the localization in membrane domains of the epitope-tagged, fluorescent version of thyrotropin-releasing hormone receptor (VSV-TRH-R-GFP) expressed in HEK293 cells. Our comparison of three different methods of cell fractionation (detergent extraction, alkaline treatment/sonication and mechanical homogenization) indicated that the dominant portion of plasma membrane pool of the receptor was totally solubilized by Triton X-100 and its distribution was similar to that of transmembrane plasma membrane proteins (glycosylated and non-glycosylated forms of CD147, MHCI, CD29, CD44, transmembrane form of CD58, Tapa1 and Na,K-ATPase). As expected, caveolin and GPI-bound proteins CD55, CD59 and GPI-bound form of CD58 were preferentially localized in detergent-resistant membrane domains (DRMs). Trimeric G proteins G(q)alpha/G(11)alpha, G(i)alpha1/G(i)alpha2, G(s)alphaL/G(s)alphaS and Gbeta were distributed almost equally between detergent-resistant and detergent-solubilized pools. In contrast, VSV-TRH-R-GFP, Galpha, Gbeta and caveolin were localized massively only in low-density membrane fragments of plasma membranes, which were generated by alkaline treatment/sonication or by mechanical homogenization of cells. These data indicate that VSV-TRH-R-GFP as well as other transmembrane markers of plasma membranes are excluded from TX-100-resistant, caveolin-enriched membrane domains. Trimeric G protein G(q)alpha/G(11)alpha occurs in both DRMs and in the bulk of plasma membranes, which is totally solubilized by TX-100.
Keywords: receptory thyroliberinu; radioligandová zkouška; kaveoliny; fluorescenční spektrometrie; Membrane Microdomains; Radioligand Assay; buněčné kultury; Receptors, Thyrotropin-Releasing Hormone; rozpustnost; membránové mikrodomény; Caveolins; Octoxynol; Cell Membrane; Centrifugation, Density Gradient; Immunoblotting; lidé; Detergents; Humans; Cell Culture Techniques; centrifugace - gradient hustoty; buněčná membrána; proteiny vázající GTP - alfa-podjednotky Gq-G11; kaveolin 1; Solubility; GTP-Binding Protein alpha Subunits, Gq-G11; imunoblotting; oktoxynol; Spectrometry, Fluorescence; Caveolin 1; detergenty